Osteogenic and anti-osteoporotic effects of risedronate-added calcium phosphate silicate cement. (7th July 2016) - Gong, Tianxing; Chen, Yadong; Zhang, Yixi; Zhang, Yubiao; Liu, Xinwei; Troczynski, Tom; Häfeli, Urs O
Abstract: Osteoporosis greatly impairs bone fracture restoration with bone cement because the accelerated resorption decreases the osseointegration between bone and implants. In this study, we designed a new drug delivery system based on the third generation bisphosphonate risedronate (RA) and the osteogenic calcium phosphate silicate cement (CPSC). The impact of RA on CPSC's material properties and microstructure was evaluated by different characterization methods ( μ CT, XRD, FTIR, SEM and gas sorption). In addition, in vitro biocompatibility of RA-added CPSC was evaluated (MTT assay, flow cytometry, real-time PCR). In an in vivo study of osteoporotic rabbits, osteoporosis- and bone resorption-related biomarkers were measured over time (ELISA) and local osteogenic and anti-osteoporotic effects investigated (x-ray, CT, histology, PCR arrays). RA decreased the setting rate and compressive strength of CPSC by impeding the hydration of calcium silicate. The overall porosity of CPSC was also decreased with RA. The RA-added CPSC was biocompatible and improved osteoblast proliferation and differentiation. The slow release of RA from CPSC reduced the prevalence of osteoporosis in rabbits and improved peri-implant bone formation and osseointegration. In conclusion, RA-containing CPSC demonstrates its potentials to improve fractural restoration under osteoporotic conditions and should be further engineered to increase its effectiveness in fractural restoration.